Impact of Demonetization on Stock Market Efficiency: A Study of BSE SENSEX and NSE NIFTY Index - Saluja, HS (International Journal of Computer Sciences and Engineering, 2025)
Demonetization may affect the various sectors of the Indian economy. As Demonetization affect liquidity in the economy that impacted economic activities. The change in the money supply in any economy might have affected the performance of its various sectors and might affect the Stock Market Efficiency. So, the present study empirically examines the Weak Form of Market Efficiency changes of BSE SENSEX Index and NSE Nifty Index of Indian Stock Market, due to demonetization. For this purpose daily returns of BSE SENSEX Index of Bombay Stock Exchange (BSE) and CNX Nifty Index of National Stock Exchange (NSE) will be considered.